Age-related pattern and monocyte-acquired haemozoin associated production of erythropoietin in children with severe malarial anaemia in Ghana - Abugri, James (BioMed Central, 2014)
BACKGROUND: Malaria continues to be a global health challenge, affecting more than half the world’s population and causing approximately 660,000 deaths annually. The majority of malaria cases are caused by Plasmodium falciparum and occur in sub-Saharan Africa. One of the major complications asscociated with malaria is severe anaemia, caused by a cycle of haemoglobin digestion by the parasite. Anaemia due to falciparum malaria in children has multifactorial pathogenesis, which includes suppression of bone marrow activity. Recent studies have shown that haemozoin, which is a by-product of parasite haemoglobin digestion, may play an important role in suppression of haemoglobin production, leading to anaemia. In this study we correlated the levels of erythropoietin (EPO), as an indicator of stimulation of haemoglobin production, to the levels of monocyte acquired haemozoin in children with both severe and uncomplicated malaria. There was a significantly negative correlation between levels of haemozoin-containing monocytes and EPO, which may suggest that haemozoin suppresses erythropoiesis in severe malaria. A multiple linear regression analysis and simple bar was used to investigate associations between various haematological parameters. METHODS: To examine the levels of erythropoietin in the age categories, the levels of erythropoietin was measured using a commercial Enyme-Linked Immunosorbent Assay (ELISA). Giemsa-stained blood smears were used to determine percentage pigment containing monocytes. The haemozoin containing monocytes was expressed as a percentage of the total number of monocytes. To obtain the number of haemozoin containing monocytes/μL the percentage of haemozoin containing monocytes was multiplied by the absolute number of monocytes/μL from the automated haematology analyzer. RESULTS: The levels of erythropoietin in younger children (<3 years) was significantly higher than in older children with a similar degree of malaria anaemia (Hb levels) (p < 0.005). Haemozoin-containing monocytes were relatively higher in severe malaria anaemia patients compared to those with uncomplicated malaria (p < 0.001). CONCLUSIONS: Age purportedly has a direct effect on background levels of erythropoietin. With corresponding decreased levels of erythropoietin in older children with the same degree of severe malarial anaemia, conceivably, the bone marrows of younger children with acute malaria may be less sensitive to erythropoietin.